A rare case of primary parasitic leiomyoma mimicking as ovarian mass: a clinical dilemma - Sarmalkar, Meenal; Nayak, Arun; Singh, Neha; Mehendale, Madhuri; Dixit, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Uterine leiomyomas are the most common benign pelvic tumors in women of reproductive age group. Parasitic or wandering leiomyomas are known for their rarity, atypical clinical presentation & unusual location, posing challenge in making radiological and clinical diagnosis. More recently, rise in incidence of secondary parasitic leiomyomas has been reported as a complication of laparoscopic myomectomy and morcellations. We report an interesting case of primary parasitic leiomyoma which initially seemed to be a case of ovarian tumor. A 38 year old woman presented with chief complaints of pain in lower abdomen since 4 months with abdominal swelling since 2 months with CT abdomen suggestive of 8.7x5.2 cm exophytic right ovarian neoplasm with differential diagnosis of broad ligament fibroid in pouch of douglas. She had no previous history of abdominal or laparoscopic myomectomy and no family history of genital tract and breast malignancy. On clinical examination, no mass could be palpated per abdominally but a firm mass of 8 x6 cm size was felt through posterior fornix. Intraoperatively, a solid mass with lobulated surface was noted in pouch of Douglas attached through a thin vascular pedicle to sigmoid colon. Differential diagnosis considering location of tumor and pathological examination included possibility of gastrointestinal stromal tumor or extra-gastrointestinal stromal tumor or wandering leiomyoma. However, on histopathological slide examination (using immunohistochemistry), GIST was ruled out and diagnosis of parasitic fibroid was confirmed. Therefore, while dealing with pelvic tumors with atypical clinical presentation, possibility of these rare tumors have to be kept in mind for appropriate management.